Hemodynamic effects of increased intra-abdominal pressure in critically ill children - Silveira,Letícia G.T (2021)
Abstract Objective: To evaluate the influence of intra-abdominal pressure on the cardiac index (CI) at different intra-abdominal hypertension grades achieved when performing an abdominal compression maneuver (ACM). Evaluating the effectiveness of the ACM in distending the left internal jugular vein (LIJV). Methods: Prospective observational study conducted in the PICU of a quaternary care teaching hospital. Participants underwent the ACM and the IAP was measured with an indwelling urinary catheter. At each IAH grade reached during the ACM, the CI was measured by transthoracic echocardiography and the LIJV cross-sectional area (CSA) was determined by ultrasonography. Results: Twenty-four children were included (median age and weight of 3.5 months and 6.37 kg, respectively). The median CI observed at baseline and during IAH grades I, II, III, and IV were 3.65 L/min/m2 (IQR 3.12−4.03), 3.38 L/min/m2 (IQR 3.04−3.73), 3.16 L/min/m2 (IQR 2.70−3.53), 2.89 L/min/m2 (IQR 2.38−3.22), and 2.42 L/min/m2 (IQR 1.91−2.79), respectively. A 25% increase in the LIJV CSA area was achieved in 14 participants (58%) during the ACM. Conclusion: The ACM significantly increases IAP, causing severe reversible impairment in the cardiovascular system and is effective in distending the LIJV in just over half of the subjects. Even low levels of HIA can result in significant cardiac dysfunction in children. Therefore, health professionals should be aware of the negative hemodynamic repercussions caused by the increased IAP.